The Impact of Ownership Structure on Dividend Pay-out : Evidence from Listed Companies in the Property Sector in Malaysia - Jasmine Lau, Huey Huey; Asri, Marsidi (2022)
This study investigates the relationship between the ownership structure and the dividend payout for listed firms in the property sector in Malaysia. By examining the correlations between different forms of ownership and the proportions of shareholdings held by a variety of ownership categories, this will help to provide a better picture about how the ownership structure of the companies actually affects the dividend decisions of companies. 46 listed companies from the Malaysian property sector are selected as the sample for this study, between the years 2011 and 2016. This study uses the random effect regression model to express the relationship between the ownership structure and the level of dividend payout for the relevant sample. The dependent variable is the dividend payout amount, and the independent variables include ownership concentration, institutional ownership, managerial ownership, and foreign ownership. Meanwhile, the control variables are firm size and firm leverage. Agency theory, signaling theory, Bird-in-the-Hand theory, and clientele effect theory, are used in this study. Our results show that ownership concentration and institutional ownership have a positive and significant relationship with dividend payout in Malaysia. By contrast, managerial ownership and foreign ownership revealed an insignificant relationship with the dividend payout. This study may be useful to both academics and professionals in the property and investment segments of developed and developing economies, and concludes with recommendations on potential for future legal and regulatory implications of the findings.